THE RELATIONSHIP BETWEEN MOTIVATION AND INTEREST IN ACHIEVING NON-ACADEMIC FIELDS IN NURSING STUDENT - Lisa Fatmawati; Suratmi Suratmi; Nurul Hikmatul Qowi (Universitas Airlangga, 2023)
Introduction: The current phenomenon is that the interest of nursing students in non-academic fields is still low. Apart from being required to complete academic assignments, nursing students are also expected to participate in organizational activities and be able to balance between the two. The purpose of this study was to determine the relationship between motivation and interest in achievement in non-academic fields among nursing students. Methods: This study used a correlational analytic design with a cross-sectional method using the Cluster Random Sampling technique and obtained 111 students. Research data was taken using a questionnaire to measure motivation and interest in achievement in the non-academic field. In this study, the results showed that most students had high motivation (68%) and most of the interest in achieving non-academic activities was in the high category (57%). Based on the research above, it is hoped that students will be able to develop their abilities so that they become graduates who master the branches of science and technology to fulfill national interests and increase foreign power. The analysis used was Spearman's analysis with a significance level of α <0.05. Results: The Spearman test results obtained p = 0.008 rs = 0.513, which means there is a relationship between the motivation of semester VI nursing students and their interest in achieving non-academic fields. Conclusions: Based on these results, it is hoped that motivation can be used as material for student self-evaluation so that it can increase interest in achievement in non-academic fields